Changes and variability of evapotranspiration sums in Slovakia in 1951–2021 - DAMBORSKÁ, Ingrid; LAPIN, Milan (Contributions to Geophysics and Geodesy, 2023)
Significant changes in air temperature and precipitation occurred in Slovakia during the second half of the 20th century and mainly in the first two decades of the 21st century. These changes influenced potential and actual evapotranspiration, soil moisture, and runoff in Slovakia. The article discusses changes and variability of evapotranspiration in the period 1951–2021 calculated by Budyko's method, which was modified by Tomlain for Slovakia, and due to climate change, the preparation of the evapotranspiration scenarios until the year 2100. The climatic indicator of irrigation, which shows the water's necessity to cover maximum evapotranspiration demands, was also evaluated from 1951 to 2021. We performed the model computation for 26 higher-quality stations in Slovakia. These stations are located in different climatic, especially humid conditions. The input data are air temperature and humidity, cloudiness, number of days with snow cover, and precipitation. The results of measurements and model calculations are presented in detail from stations Hurbanovo, Košice-airport, and Oravská Lesná. Changes in the normal of analysed phenomena between the 1951–1980 and 1991–2020 periods are shown in the table form for 20 selected stations because of limited space. The scenarios of potential evapotranspiration change until 2100, prepared by two regional circulation models (RCM) outputs, are presented at the end of the study. The results confirmed the growth of potential evapotranspiration in 1951–2021 and until 2100, while the actual evapotranspiration depends on soil moisture, which is mainly decreasing. The climatic irrigation index indicates the slightly increasing linear trend in Slovakia from 1951 to 2021.